Pola Asuh Orang Tua Beda Agama dalam Menanamkan Nilai-Nilai Religiusitas Kepada Peserta Didik - Sulastri, Sri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to obtain information about the parenting style of parents of different religions in instilling religious values in students at SMA Negeri 13 Depok. This study used a qualitative approach with a qualitative descriptive research method. This research was conducted at SMA Negeri 13, Depok City, West Java. Data collection was carried out using a purposive sampling technique. The results of this study indicate that the parenting style of parents of different religions that are not in line causes confusion in children. The role of parents who tend to be authoritarian will make children afraid and even more in the opposite direction. Parents are also expected to be wiser and lower their respective egos and build positive communication with children by being introduced to the two beliefs held by their parents, not providing an understanding of which religion is better. Because the values of religiosity are not only a matter of religion but how to build aqidah, worship, and morals. Parents of different religions should be prepared for the consequences of being a member of a minority religion in the family. Therefore, it takes an adult, wise, and calm attitude from parents so that children are not confused about their religious status. Because, both parents who are of different religions should have known the impact on children's development when deciding to get married. In conclusion, the role of parents is very important in shaping the personality, character, morals and education of children, parents of different religions must be prepared for all the consequences and be wiser in building communication about religiosity to children. Key words: parenting, different religious families, religious values, children, SMA Negeri 13 Depok